PROTOTYPE SISTEM KONTROL INTENSITAS CAHAYA RUANGAN BERBASIS ARDUINO NANO - Saufa, Nanda; Sufandi, Muhammad R.; Yohannes C.H.Y (Teknik Elektro Polsri, 2024)
The lighting requirements of each room are sometimes different, depending on the activities performed there. Previous research shows a relationship between lighting and work productivity. Productivity and production costs can be optimized with sufficient lighting appropriate to the type of work. Therefore, a light intensity measuring device is needed. In this research, a BH1750 digital light intensity sensor is used to make this device. This device receives light and processes the light to be sent to the Android microcontroller for display. The results show that the light intensity system works well based on the LUX value obtained.